Breathlessness and the brain: the role of expectation. Issue 3 (September 2019) - Marlow, Lucy L.; Faull, Olivia K.; Finnegan, Sarah L.; Pattinson, Kyle T.S.
Abstract : Purpose of review: Breathlessness debilitates countless people with a wide range of common diseases. For some people, the experience of breathlessness is poorly explained by the findings of medical tests. This disparity complicates diagnostic and treatment options and means that disease-modifying treatments do not always have the expected effect upon symptoms. These observations suggest that brain processing of respiratory perceptions may be somewhat independent of disease processes. This may help to explain the dissonance observed in some patients between physical disease markers and the lived experience of breathlessness. Recent findings: A body of breathlessness research using functional neuroimaging has identified a relatively consistent set of brain areas that are associated with breathlessness. These areas include the insula, cingulate and sensory cortices, the amygdala and the periaqueductal gray matter. We interpret these findings in the context of new theories of perception that emphasize the importance of distributed brain networks. Within this framework, these perceptual networks function by checking an internal model (a set of expectations) against peripheral sensory inputs, instead of the brain acting as a passive signal transducer. Furthermore, other factors beyond the physiology of breathlessness can influence the system. Summary: A person's expectations and mood are major contributors to the function of the brain networks that generate perceptions of breathlessness. Breathlessness, therefore, arises from inferences made by the brain's integration of both expectations and sensory inputs. By better understanding individual differences across these contributing perceptual factors, we will be better poised to develop targeted and individualized treatments for breathlessness that could complement disease-modifying therapies.